(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
Assessing speaking skills is a crucial aspect of language learning and communication. While reading and writing skills are often easier to assess through traditional methods, evaluating speaking proficiency presents unique challenges and complexities. In this article, it will be explored the various ways of assessing speaking, including different types of assessments, criteria for evaluation, the role of technology in assessments, and classroom strategies for effectively measuring speaking skills. By understanding and implementing these assessment methods, teachers can better support their students in developing their speaking abilities and enhancing their overall language proficiency.